Pengembangan Video Pembelajaran Berbasis Etnomatematika sebagai Media Pembelajaran - Anika Ferninda Sari; Selvi Loviana (Tapis: Jurnal Penelitian Ilmiah, 2025)
Mathematics learning at MTs Ma'arif 02 Kotagajah still relies on textbooks. As a result, students' performance in quadrilateral and triangle material is low, and their learning motivation is lacking. This research aims to develop ethnomathematics-based video teaching materials using cultural objects from Lampung—such as traditional houses, tapis cloth motifs, floor patterns and movements of the Sigeh Pengunten dance, and the shape of the Siger Tower—to help students better understand the concepts of quadrilaterals and triangles. The study evaluates the materials in terms of their validity and practicality. This research is classified as research and development (R&D). It follows the ADDIE development model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. During the Implementation stage, only a limited trial was conducted. The instruments used in this study included validation questionnaires completed by media and material experts to assess validity, and a student response questionnaire to assess practicality. The results show that the quality of the developed product falls into the "very feasible" category. This is supported by an average score of 3.38 from the material expert and 3.45 from the media expert. In terms of practicality, based on the responses of nine students, the product falls into the "very practical" category with an average score of 3.58.